you must use parentheses for properly formatting question. otherwise expressions and equations are likely to be misunderstood.

Log in to add a comment

Log in to add a comment

=(1+x^b-a+1+x^a-b)/(1+x^a-b)(1+x^b-a)

=(2+x^b-a+x^a-b)/(2+x^b-a+x^a-b)

=1

=(2+x^b-a+x^a-b)/(2+x^b-a+x^a-b)

=1

The Brainliest Answer!

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.